Indo-Pacific Concept : Juggling for Clarity - Hussain, Nazia (2018)
There is no consensus on what the Indo-Pacific concept will cover. It is not clear what kind of structure is needed for such an Indo-Pacific construct. Nevertheless, the main protagonists behind the Indo-Pacific concept continue their diplomatic efforts to crystalise such a strategy. ASEAN remains non-committal even though it has reasserted ASEAN centrality.